English Second Language Strategies For Teaching Irregular Plural Noun Morphological Inflection - Nephawe, Farisani Thomas (e-Journal of Linguistics, 2022)
Nouns are one basic component of the syntactic category of the English language because they can be used as subjects, direct objects, indirect objects, subject complements, object complements, appositives, or adjectives of sentences. Transforming regular nouns from singular to plural forms is comprehensible since the usual patterning is used. Converting irregular nouns from singular to plural forms causes difficulties to non-native learners of English since conversion does not follow the usual patterning. The study examined English second language strategies for teaching irregular plural noun morphological inflection to Grade 8 learners. The researcher used a quantitative research design because the results could be analysed mathematically and statistically. A probability technique was used to randomly sample 25 participants whose ages ranged from 14 to 16 at Ndaedzo Secondary School in Limpopo Province, South Africa. A statistical Package for Social Sciences version 22 was utilised to interpret the findings. Initially, the participants were incompetent in this regard but after utilising the ‘irregular plurals reversi memory game’, and ‘irregular plural nouns in movement game’ strategies, learners’ performance improved remarkably. The research recommends teaching irregular plural noun morphological inflection using the games.